What Does Job Applicants' Body Art Signal to Employers? - Stijn Baert; Jolien Herregods; Philippe Sterkens (Institute of Labor Economics (IZA), 2023)
In this study, we present a state-of-the-art scenario experiment which, for the first time in the literature, directly measures the stigma surrounding job candidates with tattoos and piercings using real recruiters. We find that job candidates with body art are perceived as less pleasant to work with, less honest, less emotionally stable, less agreeable, less conscientious and less manageable. This goes hand in hand with lower hireability for men with body art but not for women. Compared to candidates who reveal obesity, a characteristic we also randomise, those with body art score better overall in terms of hireability and rated personality, similar in terms of rated taste to collaborate but worse in terms of rated direct productivity drivers.
Keywords: C91; J24; J71; 330; body art; obesity; stigma; personality; hiring; taste discrimination; statistical discrimination